Percutaneous transluminal septal alcoholization for the treatment of refractory hypertrophic obstructive cardiomyopathy: initial experience in the Federal District - Evandro César Vidal Osterne; Tamer Najar Seixas; Walter Paulo Filho; Ernesto Misael Cintra Osterne; Otoni Moreira Gomes (Arquivos Brasileiros de Cardiologia, 2003)
OBJECTIVE: To analyze the efficacy of percutaneous transluminal septal alcoholization in the treatment of refractory obstructive hypertrophic cardiomyopathy (HOC). METHODS: The patients were referred for alcoholization after Doppler echocardiography. Before and after alcoholization, the intraventricular pressure gradient was recorded. Alcoholization was performed with a 3mL injection of absolute alcohol through a coronary angioplasty balloon catheter. The procedure was concluded after a significant reduction or abolition of the pressure gradient. RESULTS: Of 22 patients, 18 (81.8%) successfully concluded the procedure with a reduction in intraventricular pressure gradient at baseline (from 67.6±24.2 mmHg to 3.8± 1.9 mmHg, p<0.005) and after extrasystole (from 110.4± 24.2 mmHg to 9.6±2.6 mm Hg, p<0.005). A significant reduction in mean interventricular septal thickness (from 2± 0.3 mm to 1.7±0.2 mm, p<0.005) and in peak pressure gradient (from 90.7±23.5 mmHg to 6.1±1.4 mmHg, p<0.005) was observed on Doppler echocardiography after 6 months, when all patients were in functional class I. The most frequent acute complication, present in 11% of the patients, was the need for definitive pacing implantation. Relapse of the symptoms and reappearance of the pressure gradient occurred in 16.6% of the patients. One patient (5.5%) died probably due to a diffuse coronary spasm prior to the procedure, and another died suddenly on late follow-up. CONCLUSION: Percutaneous transluminal septal alcoholization is effective and safe in the treatment of HOC.